(untitled) (European Journal of Interdisciplinary Research and Development, 2025)
The article studies the impact of noise as one of the environmental factors on human health. The main sources of noise in populated areas are considered to be motor vehicles, trains, air transport, and manufacturing enterprises. According to the results, due to noise in cities, life expectancy has decreased by 8-12 years. It is recommended to develop practical recommendations and guidelines for protecting people from noise.